An Expedient Total Synthesis of Chivosazole F: an Actin‐Binding Antimitotic Macrolide from the Myxobacterium Sorangium Cellulosum - Williams, Simon (John Wiley and Sons Inc., 2016)

(untitled) (Angew Chem Int Ed Engl)
A unified strategy for the chemical synthesis of the chivosazoles is described. This strategy is based on two closely related approaches involving the late‐stage installation of the isomerization‐prone (2Z,4E,6Z,8E)‐tetraenoate motif, and an expedient fragment‐assembly procedure. The result is a highly convergent total synthesis of chivosazole F through the orchestration of three mild Pd/Cu‐mediated Stille cross‐coupling reactions, including the use of a one‐pot, site‐selective, three‐component process, in combination with controlled installation of the requisite alkene geometry.